Currency crisis theories: Some explanations for the Russian case - Tuomas Komulainen (Bank of Finland, Institute for Economies in Transition (BOFIT), 1999)
The paper examines currency crisis theories and applies them in searching for the main causes of the Russian crisis.We first study the determination of the exchange rate and then the first and second generation theories on currency crisis and finally the recent theoretical discussions of the Asian crisis.The main reason for the Russian crisis was the long-standing federal budget deficit.During the last years the deficits were financed mainly via short-term domestic debt.This created expectations of government insolvency and central bank financing.Moreover, the Russian economy has its own basic weaknesses, which render the country incapable of growth and prone to crisis.The Asian crisis was a trigger for the Russian crisis.Lower prices for Russian export products, inadequate financial regulations and lack of information in emerging markets in general are factors explaining this contagion effect.But the main mistakes that led to the crisis were those of the Russians themselves - the federal budget deficits.Thus the repair work should also start from there.
URN:NBN:fi:bof-201408071960
Keywords: 330; currency crisis; Russia; budget; contagion